The many roles of cathepsins in restenosis - Hai Long Wang; Megumi Narisawa; Pan Wu; Xiangkun Meng; Xian Wu Cheng (Heliyon, 2024)
Drug-eluting stents (DES) and dual antiplatelet regimens have significantly improved the clinical management of ischemic heart disease; however, the drugs loaded with DES in clinical practice are mostly paclitaxel or rapamycin derivatives, which target symptoms of post implantation proliferation and inflammation, leading to delayed re-endothelialization and neo-atherosclerosis. Along with the treatments already in place, there is a need for novel strategies to lessen the negative clinical outcomes of DES delays as well as a need for greater understanding of their pathobiological mechanisms. This review concentrates on the function of cathepsins (Cats) in the inflammatory response and granulation tissue formation that follow Cat-induced damage to the vasculature scaffold, as well as the functions of Cats in intimal hyperplasia, which is characterized by the migration and proliferation of smooth muscle cells, and endothelial denudation, re-endothelialization, and/or neo-endothelialization. Additionally, Cats can alter essential neointima formation and immune response inside scaffolds, and if Cats are properly controlled in vivo, they may improve scaffold biocompatibility. This unique profile of functions could lead to an original concept for a cathepsin-based coronary intervention treatment as an adjunct to stent placement.